Presumed Sturge Weber Syndrome in a Haitian Boy: A Case of Delayed Diagnosis - Gian Paolo Giuliari; Ama Sadaka; Maria Angelica Cortez; Adalgisa Corona (Case Reports in Ophthalmological Medicine)
Purpose. To report an untypical presentation of a presumed Sturge-Weber Syndrome (SWS), and to highlight the indispensable value of thorough clinical examination as primary means for proper diagnosis and management. Methods. Chart review. Results. A 7 year-old boy, with a long history of ocular symptoms and an unspecified ocular surgery, presents with a painful blind left eye. Based on clinical examination, the suspicion of SWS was raised. The presentation was not typical in the sense that no evident port-wine stain was observed on the face. However, facial asymmetry and gum discoloration were guiding clinical clues to pursue further investigations. Unfortunately, due to poor treatment response, the patient underwent enucleation. Tissue pathology revealed diffuse choroidal hemangiomas, consistent with the diagnosis of SWS. Conclusion. SWS presents with hamartomatous malformations and venous dilation affecting the skin, central nervous system and eye. The ocular involvement may vary, with the most common complications being glaucoma, buphthalmos and diffuse choroidal hemangiomas. This case report helps remind physicians of the importance of a thorough clinical examination, and highlights the ophthalmologists’ responsibility of examining beyond the eye.